A Case Study on Pemphigus Vulgaris - Rabita Nur Mannan; Afsana Chowdhury; Afia Mahmuda Khan; Fannana Nowshin; Alam, Md Tarek (Bangladesh Critical Care Journal, 2023)
Pemphigus vulgaris is a chronic autoimmune mucocutaneous disease that is primitively demonstrated in the form of intraoral lesions extending to other mucous membranes and the skin. The origin of pemphigus vulgaris is unknown, even though the disease has prompted considerable interest. It is marked by the existence of circulating IgG antibodies directed against desmosomes, which are skin components that retain particular layers of skin bound to one another. When desmosomes are attacked, the skin layer separates, and the clinical presentation resembles a blister. Oral lesions are vesiculobullous at first but easily rupture, with new bullae attempting to form as the older one’s rupture and ulcerate. A biopsy of perilesional tissue and histological and immunostaining examination is required for a correct diagnosis. The current standard of treatment relies mainly on systemic immunosuppression with corticosteroids, azathioprine, or other adjuvants, but newer therapies with possibly fewer adverse effects also seem promising. Bangladesh Crit Care J September 2023; 11 (2): 137-139